Keilmuan Guru, Keteladanan Adab, dan Pendidikan Keagamaan: Kajian Teoritis Kompetensi Pendidik dalam Perspektif Pendidikan Islam - Sudiarto Sudiarto; Joko Subando (TSAQOFAH, 2026)
Educator competence in Islamic education is not only based on mastery of knowledge but also on exemplary adab and the ability to internalize religious values in the learning process. This article aims to theoretically examine three main components of educator competence in Islamic education, namely teachers’ scholarly competence, teachers’ exemplary adab, and religious education. This study uses a library research method with a descriptive-analytical approach to various relevant literature sources. The results of the study show that teachers’ scholarly competence includes mastery of the dimensions of Islamic knowledge, pedagogical competence, and adaptive ability in response to developments in the digital era. Teachers’ exemplary adab plays an important role in shaping students’ character through the internalization of values, attitudes, and behaviors that reflect Islamic morality. Meanwhile, religious education functions as a comprehensive medium of transformation that includes cognitive, affective, and psychomotor dimensions in forming insan kamil. The conclusion of this study affirms that teachers’ scholarly competence, exemplary adab, and religious education constitute a mutually reinforcing unity: scholarly competence serves as the foundation for the validity of knowledge transfer, exemplary adab serves as a bridge for value internalization, and religious education serves as a means of forming a complete Muslim personality. The implications of this study indicate the importance of strengthening educator competence integratively so that Islamic education can produce a Muslim generation that is knowledgeable, well-mannered, and pious.